Penerapan Metode Kontekstual Untuk Meningkatkan Kemampuan Menulis Cerita Pendek Siswa Kelas XII IPS-3 SMA Negeri 3 Bojonegoro Tahun Pelajaran 2011/2012. - Susanto Susanto (Jurnal Pendidikan Edutama, 2014)
Abstract: Implementation of Contextual Method for Improving Writing Skill of Short Story Class-XII IPS 3 SMA Bojonegoro Academic Year 2011/2012. Writing short stories for high school students is considered a difficult activity. Trouble to write his ideas properly. It is also experienced by students of SMA Negeri 3 Bojonegoroclass-XII IPS 3. In this study using contextual learning methods, namely the method of selecting information based on the needs of individual students. The results show contextual application of the method can improve the quality of student learning outcomes writing short stories class XII IPS 3 SMAN 3 Bojonegoro school year 2011/2012. This isindicated by the increase in the percentage of students who achieve a range of 85-100. For comparison the results of short stories written in the early reflections only 11.42%, i.e. 11.42%Â  first cycle, whereas 28.57% in the second cycle. So also in the range of 0-44 also decreased. For comparison, the pre-action is 20.01%, 14.30% first cycle, second cycleand 14.30%.Key words: Contextual Method, Learning Writing, Short Story.